Design and fabrication of portable workbench / Mohamad Halim and Wan Hussin Wan Ahmad - Halim, Mohamad; Wan Ahmad, Wan Hossin (1986)
Broadly speaking, the bench may be regarded as a tool, especially when considered with its various attachments for holding and clamping material during the numerous operations known as bench work. There is hardly a shop of any size that does not require a workbench, and it truly has been said that the workbench is the heart of the home workshop. Thus, the workbench will be one of the first things needed. Usually, the height of the bench should be regulated to the character of the work to be done and to the height of the person who is to use it. One of the simplest benches to build is a portable work bench with screwed joints. Most of the materials used for making this Portable work bench are mild steel. This is because it is cheap, easy to be machine and available. Portable workbench can be used for holding the workpiece for sawing, filing, hammering, carving, drilling, making screw thread by using tap and die, etc. It has only two legs and can be set up to the wall or column of the house.